Status Seeking Behavior of the Poor: A Study on India - Sugata Marjit; Sattwik Santra; Koushik Kumar Hati (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper is the first attempt towards directly testing the existence of status seeking behavior of the poor for a developing economy, India, with the help of a large dataset. The paper empirically validates status consciousness among the relatively poor for both rural and urban areas across the states of India. The hypotheses that inequality impacts consumption patterns via status effect turns out to be statistically significant. Households in the majority of the states, under various specifications, demonstrate concern for status. We explore in detail the extent of this status effect for different sections of the population.
Keywords: D01; D12; C13; 330; status; consumption pattern; inequality; poverty